A bizarre presentation of pancreatitis with Bryant’s sign - Erdem Barış Cartı; Ahmet Deniz Uçar; Erkan Oymacı; Nazif Erkan; Mehmet Yıldırım; Ömer Özütemiz (Turkish Journal of Gastroenterology, 2019)
-